Synthesis, photocatalytic degradation and antibacterial properties of selenium or silver doped zinc oxide nanoparticles: A detailed review - Ifijen, Ikhazuagbe H.; Maliki, Muniratu; Anegbe, Bala (OpenNano, 2022)
Zinc oxide nanoparticles (ZnO NPs) have been the subject of extensive research due to their peculiar physical and chemical properties. Numerous studies have used their NPs as photocatalytic and antibacterial agents because of their high surface-to-volume ratio, miniature size, antimicrobial activity, and semiconducting properties. However, some of the aforementioned features also exhibit limitations in ZnO NPs. It seems possible to circumvent these limitations and increase the utilization of ZnO NPs by doping them with silver and selenium elements. Therefore, a thorough review of the use of selenium or silver doped ZnO NPs for photocatalytic and antibacterial objectives was conducted in this study. Additionally, emphasis was placed on the synthesis of ZnO NPs doped with silver or selenium using principally sol-gel, mechanochemical, and green techniques. The results showed that doping ZnO NPs with selenium or silver NPs considerably improved some intrinsic qualities as ROS production capability, bandgap, stability, etc., which consequently improved their photocatalytic and antibacterial features. As a result, they excelled at the photo-catalytic breakdown of organic pollutants and the treatment of bacterial illnesses. [Display omitted]